Valletta dumps V-licence road pricing scheme - Maria Attard; Marcus Enoch (2007)
On 1 May 2007, the City of Valletta in Malta became one of a small but growing number of cities worldwide to introduce a form of road user charge in a bid to reduce traffic congestion and improve the air quality and the level of economic activity within the historic capital city. This article explains how and why the so-called Controlled Vehicular Access scheme has been designed and developed and looks at some of the challenges ahead.